The Philippine economy in the face of external shocks - Bautista, Maria Socorro Gochoco (Asian economic papers.)
The Philippines has a unique economic history relative to its neighbors. It is less open to trade and has been unable to attain and sustain high rates of growth. Today, globalization and participation in the global economy primarily means the export of labor rather than goods. The Philippines' reliance on remittances from its cadre of overseas Filipino workers has become the main pillar of its growth and development strategy. Going into the period of the global crisis, the Philippines had robust growth relative to its historical average and a strengthened banking system. The effects on the real sector intensified in the last quarter of 2008. While there are continuing attempts to use expansionary monetary and fiscal policy to spur the economy, the ability of the Philippines to pursue such expansionary policies may be limited by the still relatively high inflation and the government's historically weak fiscal position. Although it appears that the Philippines will muddle through and survive the current global crisis, it will continue to face the daunting task of effectively leveraging for long-term growth and development.